SELEKSI PEMILIHAN MATERIAL UNTUK TABUNG ROKET RX 420 - Sumaraw, Elvis A (BRIN Publishing, 2010)
A Calculation to select the material being used for RX 420 rocket has been conducted. The selection is applied to 3 kinds of tube material i.e. SS 17-7 PH steel, ASTM A312 AISI TP304L steel and AISI 4130 steel. By inputing data of tensile strength material, strain acting on the tube, tube diameter and tube length; the size of the tube can be calculated. The thicker tube and the lightest tube are then selected to be used. From the calculation result of SS 17-7 PH steel material, the tube with the thick of 1,8 mm (safety factor, k=2) with the tube weight of 85,458 kg are the most convenient materials applied; due to the thicker (1,8mm) and the lightest (85,458 kg) with the tensile strength of 900 MPa. If ASTM A312 AISI TP304L steel material is used , then the tube thick proposed is 2,8 mm, with the tube weight of 131,7 kg. If AISI 4130 steel material is used, then the tube proposed is 3 mm, with the tube weight of 142,4 kg.